Sexuality reimagined: MSM in modern India - Tandon, Shailja (New Delhi, India: Ane Books Pvt. Ltd., 2023)
The book examines how medical knowledge is produced around bodies that do not fit in the heteronormative framework of the state's rationale and processes. The marginal bodies studied in this research are termed MSM, men who have sex with men, categorized as a high-risk group in the backdrop of HIV/AIDS. These Queer bodies entered the registers of epidemiology and governmentality. This classification is the point of departure for the book. The book interrogates and asks how does a sexual subject become a political question? To answer this political trajectory, the book analyses the category of risk in biomedicine. It investigates how the category of risk becomes critical to the Indian state's rationale and policies wherein, through the ambit of health and population, sexuality is managed. Unearthing the sexual politics in South Asia, the book, based on rich empirical evidence derived from the lived experiences of MSM, narrates the construction of sexual subjectivity and masculinity. The process of construction occurs in negotiation with the Indian state, bringing forth the dimension of the Indian state as a medico-legal governmentality regime and how MSM takes on the identity of a medicalized subject. Shailja Tandon completed her M.Phil. in Political Science from Jawaharlal Nehru University, Delhi. She is a social/urban sector professional with five years of research experience in social and public policy, spanning fields like changing urban space (from rural, peri-urban to urban), social inequalities and social security schemes, refugees, gender inequalities and empowerment with a focus on sexual minorities, human capital for development outcomes, and democratic participation and citizen behavior. She is currently coordinating the Knowledge and Practice Group of the Foundation for Creative Social Research, an intellectual initiative to create a discursive platform for interaction among academics, writers, artists, poets, social activists, and policymakers. Currently, she is a Senior Research Associate at Lead at Krea University.
Keywords: Sociology; Sex; Gender Studies; Feminist theory; Political Theory; Sexuality- India; South Asia -- Masculinities; South Asia -- Sexualities